Dampak Paparan Kebisingan dan Getaran Mesin Kapal terhadap Kesehatan Tenaga Kerja: Studi Literatur dan Rekomendasi Pengendalian K3 - annisa, retno; Annisa Nurlisti, Retno (Blueprint Journal, 2025)
The working environment on board a ship, especially in the engine room, has high levels of noise and vibration due to the operation of the main and supporting engines. Exposure to noise and vibration in the ship's engine room is a significant risk factor for the health of the crew, which can cause hearing loss, musculoskeletal disorders, work stress, and decreased productivity. The study was conducted by collecting data on noise levels (using a sound level meter) and vibration (using a vibration meter) in the area. Exposure to noise and vibration in the ship's environment is a serious threat to the health of the crew that requires a comprehensive K3 approach. The noise in the engine room is above the NAB, which is 85 dB, so PPE is needed to reduce the noise level. The combination of engineering, exposure management, and proper use of PPE (ersonal protective equipment) has been shown to reduce health risks by up to 60% based on selected studies.